Short communication Cholinesterase inhibitors for Parkinson’s disease-related visual hallucinations unresponsive to atypical antipsychotics - Sobow, Tomasz (Archives of Medical Science, 2007)
Introduction: Considering lack of accepted guideline in cases of Parkinson’s disease-related visual hallucinations with poor response or intolerance to antipsychotics, and their possible cholinergic pathogenesis, the trial with cholinesterase inhibitors seems to be legitimated. Material and methods: Five patients with PD (with or without dementia) complicated by VH and unresponsive to atypical antipsychotics were offered a 12-week, open-label trial of a cholinesterase inhibitor. Results: All 5 subjects completed the trial with no major adverse effects and, noteworthy, no discontinuations due to adverse events. VH resolved in 4 subjects and were markedly diminished in one person. Neither changes in UPDRS scores nor exaggeration of subjective complaints about extrapyramidal symptoms were noted during treatment. Conclusions: Cholinesterase inhibitors, rivastigmine or donepezil, might represent a useful alternative to antipsychotics for patients with PD accompanied by VH even in the absence of dementia.